2019
DOI: 10.1371/journal.pmed.1002923
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the optimal growth charts for use in a preterm population: An Australian state-wide retrospective cohort study

Abstract: BackgroundPreterm infants are a group at high risk of having experienced placental insufficiency. It is unclear which growth charts perform best in identifying infants at increased risk of stillbirth and other adverse perinatal outcomes. We compared 2 birthweight charts (population centiles and INTERGROWTH-21st birthweight centiles) and 3 fetal growth charts (INTERGROWTH-21st fetal growth charts, World Health Organization fetal growth charts, and Gestation Related Optimal Weight [GROW] customised growth charts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
2
24
1
3
Order By: Relevance
“…That is, identifying the chart that when applied to the local population yields weight percentiles that follow a normal distribution centered at approximately the 50th percentile, and identifies approximately 10% of the low-risk population as being below the 10th percentile and above the 90th percentile, and approximately 5% of the population as being below the 5th percentile and above the 95th percentile. An example of this approach is provided in Figure 3; (2) outcome-based validation: finding the chart for which the diagnosis of SGA has the best predictive value for adverse outcomes related to FGR.. 211,221 While this approach seems compelling, interpretation of the predictive value of the different charts for adverse outcomes may be challenging, as there is a trade-off between detection rate and false positive rate for adverse outcomes. 221 (Figure 4).…”
Section: How To Choose the Best Chartmentioning
confidence: 99%
“…That is, identifying the chart that when applied to the local population yields weight percentiles that follow a normal distribution centered at approximately the 50th percentile, and identifies approximately 10% of the low-risk population as being below the 10th percentile and above the 90th percentile, and approximately 5% of the population as being below the 5th percentile and above the 95th percentile. An example of this approach is provided in Figure 3; (2) outcome-based validation: finding the chart for which the diagnosis of SGA has the best predictive value for adverse outcomes related to FGR.. 211,221 While this approach seems compelling, interpretation of the predictive value of the different charts for adverse outcomes may be challenging, as there is a trade-off between detection rate and false positive rate for adverse outcomes. 221 (Figure 4).…”
Section: How To Choose the Best Chartmentioning
confidence: 99%
“…Of particular concern is that Intergrowth-21st charts underestimate the rate of SGA compared to Fenton charts, which is of relevance in a lower socioeconomic community such as is the case with our study [15]. In our own state of Victoria, a recent statewide survey of 28000 births concluded that "intrauterine charts appear to be the most sensitive in the detection of SGA infants at increased risk of adverse perinatal outcomes" [16]. On evaluation, we opted to remain with the 2013 Fenton growth charts as we are currently using these on a day to day basis in our SCN and our previously published study [11] used 2013 Fenton growth charts-thus allowing a valid comparison of results with this study.…”
Section: Discussionmentioning
confidence: 60%
“…We found that the normative INTERGROWTH-21 st birthweight distribution is left-shifted compared to Australian population centiles, yielding a much lower proportion of babies with birthweight <3 rd and <10 th centile. While this will identify the most severely growth restricted infants, thereby minimising the number of constitutionally small babies within the lower centiles, it will come at the expense of missing many growth restricted babies at high risk of adverse outcome [26,27]. We also showed that, when using a prescriptive birthweight standard, the effect of targeted earlier delivery of FGR led to almost total elimination of babies with birthweight <3 rd centile over time at late term gestations.…”
Section: Plos Onementioning
confidence: 74%